Bannwarth Syndrome: A Rare Manifestation of Pediatric Lyme Neuroborreliosis - Dutta, Ankhi; Hunter, Jill V; Vallejo, Jesus G (The Pediatric infectious disease journal, 2021)
Lymphocytic meningoradiculitis (Bannwarth syndrome) is a rare manifestation of Lyme neuroborreliosis in children. It is the most common clinical manifestation of early Lyme neuroborreliosis in adults in European countries where the disease is endemic but is rare in children. We report an imported case of Bannwarth syndrome in a pediatric patient and review the literature for other pediatric cases reported.